CASE MANAGEMENT OF ANTERIOR TOOTH INTRUSION DUE TO TRAUMA - Aryo Sutowijoyo; Prima Nerito (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: Dental trauma is damage that affects the hard tissue of the teeth and/or periodontal due to mechanical causes. One of the effects of trauma to the teeth is intrusive luxation, namely the movement of teeth into the alveolar bone, which can cause damage or fracture of the alveolar socket. Intrusive luxation causes the tooth crown to appear shorter. Case: An 11 year old male patient who was involved in a traffic accident came to the emergency department with complaints of being unable to walk, swollen lips and broken teeth. Case Management: The patient experienced intrusive luxation on tooth 21 and subluxation on teeth 11 and 22. The treatment carried out in this case was repositioning of tooth 21. Then splinting was carried out using wire on teeth 12, 11, 21, 22 for 1 month. Discussion: Immediate repositioning of luxated teeth is very important to accelerate tissue healing. Treatment in acute cases can be supplemented with acute management, namely administering antibiotics. In this case, antibiotics, anti-inflammatories and calcium are given to speed up tissue healing and reduce the risk of complications in the tissue. Conclusions and Suggestions: immediate repositioning, accompanied by wire splints and administration of antibiotics provide good results in the treatment of cases of intrusive luxation due to accidental trauma.